Cognitive development after perinatal unilateral infarctions: No evidence for preferential sparing of verbal functions. (March 2022) - Gschaidmeier, Alisa; Heimgärtner, Magdalena; Schnaufer, Lukas; Driever, Pablo Hernáiz; Wilke, Marko; Lidzba, Karen; Staudt, Martin
Abstract: Background: Even children with extensive perinatal left-sided lesions have been reported to show normal language functions based on right-hemispheric language reorganization. This reorganization can lead to deficits in originary right hemispheric functions ("crowding hypothesis"). In a previous study, however, we identified epilepsy (even when well-controlled), and not language reorganization, as the major risk factor for impaired nonverbal functions. Here, we asked whether verbal and nonverbal functions develop differently, and whether they share the same risk factors. Methods: We investigated 23 patients (11f, Md = 12.56 years) with perinatal strokes (16 left-sided, 8 with epilepsy), and 23 healthy age-matched controls (8 f, Md = 12.42years). Language functions were assessed using the Potsdam Illinois Test of Psycholinguistic Abilities, nonverbal intelligence with the Test of Nonverbal Intelligence, language lateralization with functional MRI, and lesion size with MRI-based volumetry. Results: We found no systematic difference between verbal and nonverbal skills in our patients or controls [median difference Z(PITPA)-Z(TONI): patients = −0.03, controls = −0.06]. Accordingly, verbal and nonverbal functions were strongly correlated in patients (r = 0.80) and in controls (r = 0.74). Language ability correlated significantly with epilepsy. Furthermore, in patients with epilepsies, verbal skills were significantly lower than in controls. Conclusion: In our cohort, we found no evidence for a differential effect of perinatal strokes on the development of verbal versus nonverbal functions, and, specifically, no evidence for a preferential sparing of verbal functions. Epilepsy, even when well-controlled, was confirmed as a single key risk factor for verbal functions. Highlights: Prospective study on the cognitive development of verbal and nonverbal functions after perinatal strokes. In our cohort, we found no evidence for a differential effect of perinatal strokes on the development of verbal versus nonverbal functions. Epilepsy, even when well-controlled, is a key risk factor for impaired language functions.